(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
This article development of students’ readiness for independent educational activities in the digital training environment of professional education model, provided pedagogical conditions, mechanism, improved methodology and effectiveness of pedagogical technology in the process of pedagogical experiment-testing are presented.